IMPROVING THE PERFORMANCE OF BATIK SMEs IN THE COVID-19 PANDEMIC - Dikdik Harjadi (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2022)
The COVID-19 pandemic has made the economy in Indonesia sluggish, especially for SMEs. Whereas the existence of SMEs in Indonesia is very important and considered by the government because SMEs can accommodate many workers and become a source of income for the middle and lower classes of the community. The aims of this research were look at how to improve the performance of SMEs so that they can still exist in the midst of the Covid 19 pandemic. Study was conducted on SMEs in West Java, Indonesia. Based on quantitative approach, this research used survey instrument by delivering questionnaire. The Structural Equation Modeling (SEM) was used to analyze the data. The result showed the significant relationship between Product Characteristics, Market competitive strategy, Price & Product Success Rate on Performance of SME